Diet selection in Arctic lemmings ( Lemmus sibiricus and Dicrostonyx groenlandicus ): forage availability and natural diets - Rodgers, Arthur R.; Lewis, Martin C. (Canadian Journal of Zoology, 1986)
We describe forage availability and diets of the lemmings Lemmus sibiricus and Dicrostonyx groenlandicus at Igloolik Island, Northwest Territories. Summer and winter diets of Dicrostonyx were dominated by the evergreen shrub Dryas integrifolia and supplemented by the deciduous shrub Salix arctica. Lemmus ate mainly graminoids and some mosses in summer but the reverse in winter. In both species, winter diets were similar in different habitats. Comparison with diets of lemmings in Alaska show sufficient similarity to explain the synchrony of population fluctuations over wide geographical areas. Site-specific differences occur, however, and these are accounted for by an examination of the diet selection process in each species. These differences have important implications for the demography of lemmings at different sites.